Pollen morphological study on some rare Allium L. (Amaryllidaceae) taxa in Turkey (Bangladesh Journal of Plant Taxonomy, 2019)
The pollen morphology of 10 Allium L. taxa, 6 of which are endemic to Turkey, were investigated in detail by light and scanning electron microscopy. According to LM and SEM, the pollen grains of genera were monad, monosulcate percolate, heteropolar with bilateral symmetry, 25.30 to 53,85 µm long axis (LA) and 17.55 to 36.86 µm short axis (SA), the form was prolate (mean of LA/SA ratio 1.30 to 1.70 and in polar view boat-shaped. Three types of ornamentation were determined. Striate-rugulate-perforate type in Allium longisepalum, A. oreophilum, A. anacoleum, A. microspathum, A.shirnakiense, A. purpureoviride and A. armenum, Rugulate–perforate type in A. pervariense and A. gabardagense and Rugulate–reticulate-perforate type in A. arlgirdense. Sulcus membrane ornamentations were rugulate or psilate. The sulcus extends from the distal to proximal ends in A. anacoleum, A. arlgirdense and A. pervariense. The present study on some Turkish species of Allium showed that several morphological pollen characters may possess taxonomical value.